1980
DOI: 10.1111/j.1570-7458.1980.tb02977.x
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Sound Produced by Courting Chalcidoid Males and Its Biological Significance

Abstract: Courting males of many species of chalcidoid wasps appear to produce sounds which can be recorded on tape. A few preliminary experiments were made with Nasonia vitripennis (Walk.) to investigate the biological functions, if any, of vibrating. Nasonia males can be silenced in a simple way, apparently without affecting their other courtship activities, by applying a small quantity of gum arabic on top of their thorax. Young, silenced males were as successful with courtship as untreated controls, but when older w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

1981
1981
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 4 publications
1
8
0
Order By: Relevance
“…This is further suggested by the fact that the male starts drumming and singing again as soon as the female becomes restless. Similar drumming and singing behaviour has been observed in certain chalcidoid wasps by van den Assem and Putters (1980). This is indicated by the fact that acoustic-sexual behaviour differs between G. m. morsitans, G. f. fuscipes (Rudrauf, 1977) and in G. pallidipes (Jaenson, 1979a,b).…”
supporting
confidence: 66%
See 1 more Smart Citation
“…This is further suggested by the fact that the male starts drumming and singing again as soon as the female becomes restless. Similar drumming and singing behaviour has been observed in certain chalcidoid wasps by van den Assem and Putters (1980). This is indicated by the fact that acoustic-sexual behaviour differs between G. m. morsitans, G. f. fuscipes (Rudrauf, 1977) and in G. pallidipes (Jaenson, 1979a,b).…”
supporting
confidence: 66%
“…Males of many chalcidoid wasps also produce similar sounds when they come near to a conspecific female and when they are on top of the female in the courtship position (van den Assem and Putters, 1980). Honey bees, Apis mellifera and stingless bees of the genera Melipona and Trigona also produce sounds with partially or completely folded wings and according to Woods (1956) when these sounds are produced, the wings are vibrated laterally in a kind of scissors motion.…”
Section: Resultsmentioning
confidence: 99%
“…However, it has been demonstrated that these vibrations are also produced after the wings have been removed, suggesting that only wing muscles are involved (van den Assem & Putters, 1980). The function of the male wing fanning remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…As demonstrated in L. distinguendus and some other pteromalids, species-specific vibrations are produced during wing fanning that can be interpreted as male signals towards the females. However, it has been demonstrated that these vibrations are also produced after the wings have been removed, suggesting that only wing muscles are involved (van den Assem & Putters, 1980). For example honeybees are able to produce vibrations without moving the wings (Kirchner, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The typical procedure is that the c~ chases the Q over a short distance, mounts, and takes up a frontal position on top, with his front tarsi placed on her head and his head protruding over her antennae. The male's courtship movements include a variety of limbs --e.g., wings, fore feet, antennae, mouth parts --and result in the production of a variety of stimuli --e.g., sounds (Van den Assem & Putters, 1980), tactile and chemical cues (Van den . A conspicuous component of the male's courtship is head nodding (i.e., moving the head up and down).…”
mentioning
confidence: 99%